Model Pembelajaran Realistic Mathematic Education (RME) terhadap Peningkatan Hasil Belajar Matematika Siswa Sekolah Dasar - Usklaf, Muhammad; Agus, Imaludin; Sangila, Muhammad Syarwa (IAIN Kendari, 2023)
This research aims to describe the implementation of the Realistic Mathematics Education (RME) learning model in a fifth-grade classroom at one of the elementary schools in the Bonegunu district and to improve students' mathematics learning outcomes on the subject of spatial structures. The subjects of this classroom action research are 26 fifth-grade students in the school. The research design adopts the Kemmis and Taggart model, which includes planning, action, observation, and reflection. Data collection techniques include observation, interviews, tests, and documentation. Data were analyzed descriptively qualitatively. The results show that the implementation of mathematics learning using the Realistic Mathematics Education (RME) learning model proceeded well according to the prepared plan. Students' learning outcomes in Cycle I were in the good category with a learning completeness percentage of 57.69% and an average of 66.35. It then increased to the very good category with a completeness percentage of 92.31% and an average of 87.50 in Cycle II. These findings indicate that the implementation of the Realistic Mathematics Education learning model in the classroom has a positive impact on improving students' mathematics learning outcomes in elementary school.Keywords: Realistic mathematic education (RME), student’s activity, matehematics learning outcomes.